Assessing the Effectiveness of Supervisory Management Strategies for Pod Fly, Melanagromyza obtusa in Pigeonpea - , Saleemali Kannihalli; , Narayanaswamy Jeevan; , Sahana M; , Chethan Kumar K B; , Karan Sathish; , Shankar M (Archives of Current Research International, 2024)
A field experiment was conducted during kharif 2019-20 at Zonal Agricultural Research Station, Kalaburagi, University of Agricultural Sciences, Raichur, Karnataka, India to assess supervisory management strategies for pod fly in pigeonpea variety TS 3R sown on different dates viz., 20-07-2019, 05-08-2019 and 20-08-2019. In protected plots, pod fly was managed by spraying insecticides recommended in package of practices i.e., Imidacloprid 17.8 SL @ 0.20 ml + jaggary 10 g l-1 as first spray at 10 days after pod formation and second spray with Thiamethoxam 25 WG @ 0.2 g + jaggary 10 g l-1 at 15 days after first spray with additional sprays as needed based on the damage. First spraying was done based on the incidence of pod fly i.e., when the seed damage due to pod fly crossed 5%. Subsequent sprays were taken up on need basis at 15 days interval whenever seed damage crossed 5%. Present study revealed that the protected plots had significantly lower pod and seed damage compared to unprotected plots and the need-based application of recommended chemicals effectively controlled pod fly in crop sown on 20th July. However, crops sown on 5th August and 20th August faced higher pest pressure and required three sprays, indicating that late planted crops are more susceptible to pod fly infestations and may need additional treatments to manage the increased pest load.